Analisis Faktor-Faktor Penghambat Dan Pendukung Pelaksanaan Pembelajaran PKN Pada Siswa Kelas V DI SD Negeri 060856 Medan Perjuangan - Anju Mayang Chairunnisa; Ramadan Lubis; Safran Safran (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
The research that has been carried out is entitled "Analysis of Inhibiting and Supporting Factors for the Implementation of PKN Learning in Class V Students at SD Negeri 060856 Medan Perjuangan" with the background being that there are students who feel bored in PKN learning that takes place in class, besides that this research looking for causes to arouse the enthusiasm of students in learning PKN. The purpose of this study is to identify and describe the inhibiting and supporting factors of students in the implementation of Class V PKN learning at SD Negeri 050856 Medan Perjuangan. The methodology of this research is to use qualitative methods with a descriptive approach to analysis with data collection techniques in the form of observation, interviews and documentation. The results of the study revealed that there were factors that hindered students in learning, namely: (1) students did not focus on learning PKN, (2) lack of interest of students in learning PKN, (3) there was no supporting media in learning. In addition, there are also factors that support students in learning, namely in the form of: (1) Use of active learning strategies, (2) support from parents (3) Adequate facilities. Based on the research findings, support and encouragement for students to increase their enthusiasm in learning Internships is very much needed, with educators and parents able to work together in providing support to students in learning.